ZIC2 drives colorectal cancer progression by regulating QPRT-mediated cell migration - Zheng, Liken; Liu, Hao; Yang, Ailing (Frontiers in Immunology, 2026)
BackgroundColorectal cancer (CRC) is characterized by high mortality. Zinc finger protein ZIC2 plays a dual role in various cancers; however, its clinical value of ZIC2 in CRC remains unclear.MethodsTCGA cohort data, GEO datasets (GSE39582 and GSE139555), and a CRC_10x spatial transcriptomics dataset were used for molecular feature analysis of ZIC2 to confirm its expression and clinical significance in cancer. These analyses included bulk transcriptomic analysis, single-cell transcriptomic analysis, and spatial transcriptomic analysis. Weighted gene co-expression network analysis (WGCNA) was used to identify the genes interacting with ZIC2. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to explore the potential mechanisms of ZIC2 in CRC. Cytological assays were conducted to validate the expression, function, and mechanism of ZIC2 in CRC. The effect of ZIC2 on cell migration was evaluated using cell scratch assays.ResultsZIC2 was upregulated in most cancer tissues compared with normal tissues, and high ZIC2 expression was associated with poor prognosis. ZIC2 expression of ZIC2 was positively correlated with tumor mutational burden (TMB) and microsatellite instability (MSI). Multiple tumor-related pathways were differentially enriched between high and low ZIC2 expression phenotypes in CRC, particularly the Wnt signaling pathway and stem cell–related pathways. WGCNA identified quinolinate phosphoribosyltransferase (QPRT) as a potential downstream target regulated by ZIC2. Functional validation demonstrated that ZIC2 overexpression significantly enhanced colorectal cancer cell migration and proliferation, accompanied by upregulation of QPRT. Importantly, treatment with phthalic acid, a QPRT inhibitor, partially reversed the ZIC2-induced enhancement of cell migration, indicating that ZIC2 promotes CRC cell migration through a QPRT-dependent mechanism.ConclusionZIC2 may serve as a valuable prognostic and prognostic biomarker in pan-cancer, including CRC. ZIC2 may promote the colorectal cancer progression by upregulating QPRT.